RECOMMENDATIONS FOR THE USE OF OPEN SYSTEMS NETWORK TECHNOLOGIES IN THE STUDY OF FUTURE BACHELORS OF INFORMATICS - T. Vdovychyn; U. Kohut; O. Sikora (Ìнформаційні технології в освіті)
The article presents recommendations for the use of open systems network technologies (OSNT). It determines the priority directions of the use of OSNT and the circumstances of their implementation at higher educational institutions (HEI). While modeling the process of specialist training, all its aspects (educational, scientific, organizational, managerial, educational etc.) should be analysed. It is important to use open systems network technologies in the educational process at HEI. The transition to the system of organization of educational process with the use of OSNT is theoretically grounded. Such transition requires that a university present an information package about the institution and a student coordinator for the educational process. The article focuses on the process of training of Bachelors of Informatics. It is determined that informing of future Bachelors of Informatics about the organization of their study program, peculiarities of training quality control and managerial activity is carried out at all levels of management: chair, dean’s office, university administration. The peculiarities of the use of OSNT by all the participants of the educational process of the HEI are described. It is substantiated that OSNT fully accompany the process of students training. The academic staff forms the educational load and elaborates the educational and methodical complex of subjects. The administration of HEI and educational and administrative staff of HEI (enrollment committee, the formation of lessons schedule, library, personnel department) also have important functions in the process of students training. OSNT selection for the higher educational institutions should be performed according to the following characteristics: (i) management supporting; (ii) commitment to the end-user; (iii) establishment of three-dimensional interaction; (iv) user service.